Pre-translocation health assessment and conservation priorities for Conolophus iguanas in the Galapagos Islands, Ecuador : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Conservation Biology, Massey University, Auckland, New Zealand - Heng, Colin Zhao Jie (Massey University, 2021)
The conservation of biological diversity worldwide requires an understanding of the biology of species and ecosystems to protect, as well as information sharing between scientists and managers. However, it is common to encounter delays between the production of research results and the refinement of conservation plans based on these findings. The Galapagos terrestrial iguanas (Conolophus spp) are a group of three endemic species in the Galapagos Archipelago, Ecuador. In the last 90 years there have been numerous actions with the goal to preserve these species, significantly the reintroduction of Galapagos land iguanas (Conolophus subcristatus) to various islands in the archipelago. However, important aspects of the biology of Galapagos terrestrial iguanas remain undocumented. In this thesis I present the first analysis of pre-translocation effects of ectoparasites on the body condition of Galapagos land iguanas on the island of Seymour Norte. This analysis is however incomplete due to significant logistical challenges imposed by the global 2019 COVID-19 pandemic. I also present information on the body condition and approximate density of the elusive Pink iguana (Conolophus marthae) on Wolf Volcano, and a preliminary description of the status of Galapagos land iguanas reintroduced to Santiago Island. Once again, the major logistical difficulties imposed by the ongoing COVID-19 global pandemic mean that the results presented in this thesis are only preliminary as there no possibility to complete data collection in the field at the time of submission of this thesis. Nevertheless, I hope that some of the information contained in this thesis can assist the Directorate of the Galapagos National Park in its mission to preserve all the known populations and species of Galapagos terrestrial iguanas.
Keywords: 410401 Conservation and biodiversity